INCOME AND ACADEMIC ACHIEVEMENT AMONG ELEMENTARY STUDENTS IN RURAL ODISHA - Malik, Manas Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Indian constitution has an objective to guarantee social, political and economic justice to all regardless of caste, creed and religion. When it was framed, it was visualized that, development in education along with other allied sectors will play a vital role in bringing about desirable changes in the country, where in opportunity is provided to develop critical thinking and self-determination. Hence the programmes in India intended to bring in equalization of educational opportunities face specific and unique problems. Lack of access to government schools, lower political participation and representation of underprivileged groups in governance structure, under representation in mainstream economic activities and inequalities in access to credit are possible reasons for educational backwardness. Education represents one way to break out of cycles of poverty and distress, but it is also a by-product of such economic conditions prevails among Dalit children than Non-Dalit counterparts. The study intense to reveal the relationship between Dalit than Non-Dalit children in accordance with Income and Academic Achievement in elementary level of education in Odisha.As education is an important agent of change; it is worth knowing academic achievement among deprived communities. This study and regionspecific data will provide an important data base for understanding the educational achievements and challenges.